Synergistic response of Azadirachta spp. and Syzygium spp. on some fungi due to immunomodulators - Dassharma Kakoli; Bagkar Pratik; Ravnang Pratik (International Journal of Life Sciences, 2015)
Medicinal herbs act as immunomodulators supporting the body’s immunity system to deal with allergens. Since Neem and Clove are great source of traditional medicines, they were taken up as tool for our study to evaluate their lethal effects on three fungi- Aspergillus, Candida and Penicillium spps. using ethanolic and acetone solvent extracts through Disc Diffusion method. It was clearly observed that Neem had better efficacy as compared to Clove since it showed appreciably higher potency in both the extracts. However the results of the comparative potential of Neem in three fungi was found to be most in Penicillium followed by Aspergillus and least in Candida. Another method was carried out using Well Diffusion method where three different ratio concentrations of Clove : Neem (1:2, 1:1, 2:1) were taken using ethanolic and acetone extracts separately and tried on three organisms at individual level. The result noted showed best antifungal response in 1: 1 followed by 1 : 2 and minimum effect by 2 : 1 which hinted the possibility of the enhanced effect of Clove when paired with Neem. The above experiments proved Neem to be a better fungicide and also yielded enhanced effect when in mixture with Clove. The Spectrophotometric readings for the presence of Flavonoids, phenols, and sterols provided us with the information which showed the concentration of phenols to be more than the others which lead us to believe that in all probability phenols is the active principle behind the better efficiency of Azadirachta as compared to Clove as a fungicide and thus can be pursued as a source of alternative medicine.